Nano carbon and tungsten carbide in hydrodehalogenation of chloro-floro carbon (CFC) - Yacob, Abd. Rahim (Faculty of Science, 2009)
The importance of activated carbon as adsorbent, catalyst and catalyst support has been increased in industry and environmental applications for its special features; a very high surface area absorbency, inertness, and porosity. The surface structure and porosity of an activated carbon largely depended on the starting materials and the activation method used. In this study, activated carbons were prepared from palm kernel shell by chemical activation using zinc chloride under both nitrogen flow and vacuum condition. The effects of impregnation ratio (ZnCl2 to palm kernel shell) and activation condition on the surface properties of carbons were carefully studied in order to optimize these parameters. All the prepared activated carbons were characterized using FTIR, single point BET surface area, nitrogen adsorption analysis, FESEM-EDX and Thermogravimetry analysis. The selected activated carbons were used as a carbon source as well as catalyst support in the preparation of tungsten carbide (WC). The catalyst was prepared via sublimation technique where the metal precursor tungsten hexacarbonyl and activated carbon were milled together and heattreated at 700 ÂºC and 950 ÂºC in Helium flow. Two sets of WC catalysts with 6 percent and 15 percent tungsten content were prepared. The heat-treated catalysts were characterized by XRD, single point BET surface area and FESEM-EDX. The performance of the optimal prepared WC catalyst was tested on dichlorodifluoromethane, CFC-12 in hydrodehalogenation reaction. The results show that the impregnation ratio and the activation conditions had significant effect on the properties of activated carbon prepared. In this study the activated carbon prepared with ZnCl2 impregnation ratio of 1:1 under nitrogen flow (AC-1Z-N) showed the highest surface area, 878 cm2g-1 with micropore volume around 0.36 cm2g-1. While, the catalyst with 15% tungsten content supported on AC-1Z-N showed the highest formation of tungsten carbide and found to be very active in the hydrodehalogenation reaction of CFC-12.